IBS: An economic perspective on mechanisation and automation - Siti Syariazulfa, Kamaruddin; Mohammad Fadhil, Mohammad; Rohana, Mahbub (AMER & cE-Bs by e-International Publishing House, Ltd., UK., 2018)
Incorporating mechanisation and automation in the construction process is necessary to reduce production time and costs, improve working conditions, avoiding dangerous works, allow work to be performed where people cannot do, and eventually will increase performance, and product quality. This paper discusses a preliminary study on enhancing the quality of life by adopting Industrialised Building System (IBS) focusing on the economic perspective on the use of mechanisation and automation. The sustainability principles in the IBS have always maintained the harmony between environment and construction, improve human self-respect and encourage economic development to strive for a better quality of life.